Correlation of Depression, Anxiety and Stress with Indices of Dental Caries and Periodontal Disease among 15-Year-Old Adolescents in Bandar Abbas during 2017-18 - Sara Maleki kambakhsh; Reza Masoudi; Siavash Bagheri Shirvan; Saber Babazadeh (Mashhad University of Medical Sciences, 2021)
Introduction: The present study aimed to explore the correlation of depression, anxiety, and stress with indices of dental caries and periodontal disease among 15-year-old adolescents living in Bandar Abbas during the academic year 2017-18.Materials and Methods: The present descriptive-analytical research was conducted on all 15-year-old students (n=478) in Bandar Abbas. Two individuals were employed for examination in collecting clinical data. Depression, Anxiety, and Stress Scale (DASS21) were completed by students. Then, data were analyzed using descriptive statistics along with ANOVA and Chi-squared test.Results: Of all the participants in this study, 52.8% of students were male and 47.2% were female. Furthermore, 91.3% of participants' fathers were employed. Also, 33.4% of fathers and 34.3% of mothers had an academic degree. The results indicated a statistically significant difference between anxiety, stress, and depression and simplified oral hygiene index. The majority of students were psychologically classified as average, which was also statistically significant (p<.001).Conclusion: The present study concluded that the parameters in DASS21 are correlated with oral hygiene indices (periodontitis and dental caries). Therefore, students with better psychological health have higher oral hygiene.